PENETAPAN KADAR Ã-KAROTEN PADA BEBERAPA JENIS CABE (Genus Capsicum) DENGAN METODE SPEKTROFOTOMETRI TAMPAK - Octaviani, Tri; Guntarti, Any; Susanti, Hari (Pharmaciana, 2014)
Beta carotene is provitamin essential role for vitamin A formation. Most of vitamin Asources are Ã-carotene. In the body, Ã-carotene will be converted into vitamin A. Chilies areconsidered as one of the essential food. Chillies are known as very good sources of Ã-carotene.Therefore, it is important to conduct a research in order to observe the content of Ã-carotene inthe chillies using visible spectrophotometry. Fresh chillies were extracted with a mixture ofhexane:acetone:ethanol (2:1:1) v/v using a maceration method. After the extraction process wascomplete, aquabidest was added. The extraction result was non-polar phase. It was separatedand evaporated. The residue was further subjected to qualitative and quantitative analysis102 PharmaÒ«iana, Vol. 4, No. 2, 2014: 101-109obtained. Qualitative analysis by using Carr-Price method. Determination of Ã-carotene wasconducted using visible spectrophotometry method at 452,4 nm. The qualitative test resultsshowed that the Capsicum annuum L. Var. abreviatum Fingerhuth, Capsicum annuum L. Var.Longum sendt) and Capsicum frutescens L. contain Ã-carotene. From the research, it wasobtained that the average levels of Ã-carotene on the Capsicum annuum L. Var. abreviatumFingerhuth was (10,54Â±0,07) mg/100g, Capsicum annuum L. Var. Longum sendt was(5,57Â±0,13) mg/100g and Capsicum frutescens L. was about (0,36Â±0,01) mg/100g. Statisticalanalysis using LSD test of Ã-carotene levels in the Capsicum annuum L. Var. abreviatumFingerhuth, Capsicum annuum L. Var. Longum sendt) and Capsicum frutescens L. weresignificantly different at P of 0.05.